2014
DOI: 10.1021/ma502201e
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Graphene Surface Chemistry for High-Performance Rubber/Graphene Composites

Abstract: In a rubber/filler composite, the surface chemistry of the filler is a critical factor in determining the properties of the composite because it affects the dispersion of the filler and the interfacial adhesion between the filler and rubber. In this study, we primarily focus on how graphene surface chemistry affects the dispersion of graphene and interfacial adhesion in butadiene− styrene rubber (SBR)/graphene composites and on the resultant properties of the composites. Composites that contain graphene with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
110
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(113 citation statements)
references
References 55 publications
2
110
0
1
Order By: Relevance
“…The decrease of tan % peak reflects that GO sheets have effectively immobilized NR chains near the polymer-particle interface due to favorable interfacial interactions with the NR matrix [39,57]. Meanwhile, the maximum tan % values of the composites with G2 and G1 are lower than that of G3.…”
Section: Effects Of Go Size On the Mechanical Properties Of Nr/go Nanmentioning
confidence: 98%
“…The decrease of tan % peak reflects that GO sheets have effectively immobilized NR chains near the polymer-particle interface due to favorable interfacial interactions with the NR matrix [39,57]. Meanwhile, the maximum tan % values of the composites with G2 and G1 are lower than that of G3.…”
Section: Effects Of Go Size On the Mechanical Properties Of Nr/go Nanmentioning
confidence: 98%
“…In addition, the reduction of GO can be performed in the coagulated rubber/GO compounds. The aggregation of graphene is significantly limited during reduction because the GO has already been immobilized by the rubber chains in the compounds [7,103].…”
Section: Masterbatchmentioning
confidence: 99%
“…(3) Elastomers are thermosetting polymers. The dispersion and aggregation of fillers is dependent on interfacial interactions and heat/pressure that facilitate the thermodynamically driven aggregation of the conductive fillers [7,8]. The processing of rubbers differs from the thermoforming process of plastics because the former is accompanied by crosslinking.…”
Section: Introductionmentioning
confidence: 99%
“…an increase in the Young's modulus or stress at break) are desirable, then the route of vulcanization should be followed. On the other hand, if high electrical conductivity values are the main objective, uncrosslinked materials can exhibit a very low percolation threshold and high conductivity values.Tang et al[207] have also shown recently the importance of the surface chemistry of the filler in controlling both the dispersion and interfacial adhesion between graphene produced by the in situ chemical reduction of GO and styrene/butadiene rubber, both of which affect the resultant properties of the nanocomposite. The determinant factor on the dispersion of graphene, according to their work, is the CO x fraction.…”
mentioning
confidence: 99%